Sistem Informasi Pariwisata Bali Berbasis Website dengan Metode User Centered Design - Irfansyah; Novi Dian Nathasia; Gatot Soepriyono (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Bali is a tourist destination in Indonesia that makes the country known to the world community. Currently, tourists are facing problems with information about bali tour packages and access to accommodation. Making this application using Visual Studio Code Programming as a website page, using PHP to design a dynamic website, using CSS to control the appearance of the website, and using a MySQL database as the database. The results of this Information System study can provide complete information about Bali tour packages and accommodations. By using the User Centered Design (UCD) method, the interface displays that focus on a user's needs. The results of the design of an interface are page menus, tour package menus, hotel list menus, contact menus, and login menus. Based on the results of descriptive analysis tests assisted by the Statistical Product Service and Solutions computer program as an effort to determine the response of www.baliaset.com users involving 100 samples, it was found that the highest mean was obtained in the 8th statement item of 4.50 and the lowest mean was obtained. in the third statement item is 4.13